2008
DOI: 10.1111/j.1747-0765.2008.00262.x
|View full text |Cite
|
Sign up to set email alerts
|

Characterization of the frayed edge site of micaceous minerals in soil clays influenced by different pedogenetic conditions in Japan and northern Thailand

Abstract: Radiocesium interception potential (RIP), a quantitative index of a frayed edge site of micaceous minerals, was investigated on test clay minerals (illite, kaolinite, montmorillonite and vermiculite) and soil clays formed under different pedogenetic conditions in the Kinki district of Japan and in northern Thailand to elucidate the effect of pedogenetic weathering on the amount of frayed edge site of micaceous minerals. ) compared with illitic minerals (4.3 mol kg -1 in silt size; 11.8 mol kg -1 in clay size) … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
54
0

Year Published

2013
2013
2020
2020

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 123 publications
(55 citation statements)
references
References 43 publications
1
54
0
Order By: Relevance
“…The XRD chart for the field B soil clearly shows the presence of expansible 2:1 clay minerals. Fixation of radiocesium by expansible 2:1 clay minerals (Nakao et al 2008) appears to be related to low TF values in field B. The RIP was not measured in the present experiment, so we cannot confirm this hypothesis without additional research.…”
Section: Discussionmentioning
confidence: 57%
See 1 more Smart Citation
“…The XRD chart for the field B soil clearly shows the presence of expansible 2:1 clay minerals. Fixation of radiocesium by expansible 2:1 clay minerals (Nakao et al 2008) appears to be related to low TF values in field B. The RIP was not measured in the present experiment, so we cannot confirm this hypothesis without additional research.…”
Section: Discussionmentioning
confidence: 57%
“…The contamination of paddy fields will last for a long time, because the half-life of 137 Cs is about 30 years and the mobility of radiocesium in field soils is very low (Nakao et al 2008). Moreover, paddy rice may uptake more radiocesium than other upland crops (Tensho et al 1959).…”
Section: Introductionmentioning
confidence: 99%
“…The RIP value is known to be about 0.006 mol/kg in kaolinite, one of the 1:1 phyllosilicates, while that in mica reaches 11.8 mol/kg, indicating the strong and selective affinities of Cs to FESs. 17) Indeed, scanning electron microscopy and X-ray microprobe measurements roughly confirmed that radioactive Cs is fixed only around the edge of micas. These results strongly support the selective affinity for Cs of FESs.…”
Section: Ccse Japan Atomic Energy Agency Kashiwa Chiba 277-8587 Jmentioning
confidence: 89%
“…The capacity of the "frayed edge" sites of illite and sericite is sufficient for Cs at 10 −9 mole L −1 , reflecting our present sequential desorption behavior observation that most of the adsorbed Cs was residual after the desorption treatment. On the other hand, a pure mica structure reversibly adsorbs Cs [27,28]. In the present experiments, for Cs at 10 −4 mole L −1 , most of the Cs adsorbed by illite and sericite was desorbed by the three reagent solutions.…”
Section: Adsorption Of Cs By Mineralsmentioning
confidence: 64%
“…The "frayed edge" site of kaolinite was estimated by radiocesium interception potential (RIP) to approx. 1 × 10 −8 mol g −1 [30], being lower by 1000 than that of illite [31]. Thus, approx.…”
Section: Adsorption Of Cs By Mineralsmentioning
confidence: 99%